Improving the Behavior of Loss Of Mains Protection in Electrical Distribution Networks with Distributed Generation by Using of Performance Curves - صالحة, فؤاد (Latakia University Journal -Engineering Sciences Series, 2022)
Loss-Of-Mains protection (LOM) is a requirement for connecting the generation units to the distribution network. This protection, which is based on the instantaneous reading of the frequency of the distribution network, disconnects the distributed generator only when the mains supply is cut off. Frequency change due to other reasons other than the loss of the main supply, usually, causes a failure in the work of these protections and therefore the false disconnection of the distributed generators. This paper presents a method to avoid this false disconnection by, first, deducing and drawing the performance curves of the ROCOF (Rate of Change Of Frequency) used to protect against loss of mains. Second, boundary conditions were proposed to place the performance curves between two boundary curves that confine an area representing the work area of ​​these relays. Modeling and simulation were done using MATLAB for an electrical system consisting of a synchronous distributed generator, connected to the electrical system via a power distribution line, in addition to a set of loads.